NASAKH WA MANSUKH MENURUT IMAM AS-SUYUTI DALAM PERSPEKTIF ULUM AL-QUR’AN.docx - Rima Aulia Maftukha; Wildan Setiawan (Ma'had Aly Journal of Islamic Studies, 2026)
This study examines the concept of nasakh wa mansukh according to Jalaluddin as-Suyuti within the perspective of ‘Ulum al-Qur’an. Nasakh is an important subject in the discipline of Qur’anic studies, referring to the abrogation or replacement of a legal ruling (ḥukm shar‘i) by another ruling revealed later. This research analyzes al-Suyuti’s views as presented in Al-Itqan fi Ulum al-Qur'an and Tafsir al-Durr al-Ma'tsur, as well as relevant Qur’anic verses related to nasakh wa mansukh. The findings show that, according to al-Suyuti, linguistically nasakh means to erase, replace, or transfer, while terminologically it refers to the lifting of a legal ruling by another legal evidence that comes afterward. He emphasizes that understanding nasakh wa mansukh is an essential requirement for a mufassir in order to avoid errors in interpretation and legal determination. Al-Suyuti also classifies abrogation into several forms and outlines the conditions under which it occurs. In his view, nasakh does not represent contradiction within the Qur’an; rather, it reflects divine wisdom and mercy in legislating laws gradually according to the circumstances of the community. This study highlights the dynamic nature of Islamic legislation and underscores the importance of proper methodology in interpreting legal verses of the Qur’an.